Developing Listening Materials for the Tenth Graders - Syafi’i , Muhammad Lukman (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2016)
The needs survey shows that English listening skill of the students in the tenth graders of Indonesian Islamic High School or Madrasah Aliyah is not well developed. Consequently, the listening instructional materials based on standard of content 2006 used in the classes need to be advanced. The researcher used only one try out of the product, second revision in this study was the seventh step of Borg and Gall model operational product revision. This was done based on the result of the try out, and the final product (the production of the new materials). The development used in this study consists of needs survey, developing the materials, experts and teacher's validation, revision, try out, second revision and the final product. The product is found acceptable for the tenth grade students.